Designing and Assessing the effectiveness of education through mobile application "Child Care" on knowledge, performance and satisfaction of parents of children with renal disease - Javadi larijani, Faezeh; Zolfaghari, Mitra; Mohammadi, Aeen; Javadi larijani, Amir Adel (Journal of Pediatric Nephrology, 2020)
Introduction: One of the most important diseases among children is urinary tract infection which can lead to permanent damage to the renal parenchyma with the possibility of delayed complications such as hypertension or chronic renal failure. The aim of designing and evaluating the effectiveness of education by the "Child Care of Kidneys" tool on the level of knowledge, practice and satisfaction of parents of children with kidney disease. Methods: In this quasi-experimental study, 70 parents referred to the Pediatric Nephrology Clinic in the Pediatric Nephrology Clinic were enrolled in the study in 1398 (35 received traditional training and 35 received face-to-face training by installing an application on the Android mobile phone, after 6 weeks the questionnaire was completed and the data were analyzed. The software used was version 23 of SPSS software. Significance level was considered 0.05. Results: The mean score of knowledge in both groups was equal to 6 ±1 (moderate). There was no statistically significant difference between the knowledge scores of the two groups (0.68). The performance score of the traditional training group was 12±2 (average) and the second group who were trained with the application was 13 ± 2 (moderate). There was a statistically significant difference between the performance scores of the two groups (0.02). The satisfaction score of the application was relatively good. Discussion and Conclusion: Parent education through the installation of applications on mobile phones has a very good effect on the performance and satisfaction of parents of children with kidney disease.